2018
DOI: 10.1007/s11071-018-4472-y
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear stability analysis of whirl flutter in a rotor-nacelle system

Abstract: Whirl flutter is an aeroelastic instability that affects propellers/rotors and the surrounding airframe structure on which they are mounted. Whirl flutter analysis gets progressively more complicated with the addition of nonlinear effects. This paper investigates the impact of nonlinear pylon stiffness on the whirl flutter stability of a basic rotor-nacelle model, compared to a baseline linear stiffness version. The use of suitable nonlinear analysis techniques to address such a nonlinear model is also demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 19 publications
0
18
0
2
Order By: Relevance
“…12, crucially both the bowtie LCO and the double main branches are attached to the zero main branch, and there is no homoclinic bifurcation connecting the bowtie LCO to the whirl flutter branch from each double main branch. In [31], this bowtie LCO was demonstrated through time simulations though no analysis of any kind was conducted.…”
Section: Nonlinear Analysis Of the Basic Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…12, crucially both the bowtie LCO and the double main branches are attached to the zero main branch, and there is no homoclinic bifurcation connecting the bowtie LCO to the whirl flutter branch from each double main branch. In [31], this bowtie LCO was demonstrated through time simulations though no analysis of any kind was conducted.…”
Section: Nonlinear Analysis Of the Basic Modelmentioning
confidence: 99%
“…CBM is selected for obtaining results as it enables comprehensive exploration of a range of nonlinear system steady-state behaviours, while identifying the bifurcations that interlink the branches of various solution types. The authors have previously used CBM to explore the effects of polynomial stiffness nonlinearities on the whirl flutter stability of a basic rotor-nacelle system [28,29], and a higher complexity gimballed rotor-wing model [30]. In all cases, the effects of the nonlinearities were complex, though a recurring finding was the possibility of flutter behaviour when linear analysis predicted stability.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[16] used multibody simulation to study the effect of nonlinear spring stiffness on a whirl flutter wind tunnel model using linearisation and nonlinear time simulation. Mair et al used nonlinear analysis techniques like bifurcation and eigenvalue analysis to demonstrate the effect of nonlinearities for tilt rotor gimbal stiffness [18] and propeller pylon stiffness [19] using analytical models. They concluded that in some cases there can be areas for pylon (or gimbal) stiffness which are unstable in the non-linear case but predicted as stable by the linear methods.…”
Section: Introductionmentioning
confidence: 99%